Pengaruh Profitabilitas Terhadap Pengungkapan Corporate Social Responsibility (CSR) Perusahaan High Profile - Nofrivul Nofrivul; Yeni Melia; Ade Novelino (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to examine the effect of profitability on disclosure of Corporate Social Responsibility (CSR). The research method used is quantitative research with secondary data documentation in the form of financial reports or accountability reports published by the company for the period 2016-2018. With a total sample of 24 High Profile companies listed on the IDX. The statistical analysis used was a simple linear regression analysis that was preceded by a normality and linearity test as a prerequisite for the regression test and then tested for the significance of the regression coefficient (t-test) and the correlation test. The results of the hypothesis test are profitability affects the disclosure of Corporate Social Responsibility (CSR). Keywords : Profitability, Corporate Social Responsibility, ROA, Global Reporting Initiative Index